Fungal Remediation and Subsequent Methanogenic Digestion of Sixteen Winery Wastewaters - Strong, P.J. (South African Journal of Enology and Viticulture, 2016)
Sixteen winery wastewaters were partially characterised during peak wine production. Raw wastewaters were inoculated with Trametes pubescens MB 89 to establish whether a submerged culture could be used to treat winery wastewaters, and whether fungally-treated wastewater would be rendered more degradable by secondary biological treatment using methanogenic bacteria. Additionally, laccase activity was monitored during the treatment to determine if phenolic compounds present in the wastewater would stimulate the synthesis of the fungal enzyme. Fungal treatment using T. pubescens MB 89 lowered the chemical oxygen demand (COD) and increased the acidic pH values of all wastewater samples. Five of the wastewater samples showed an increase in laccase synthesis, but the concentrations were low and did not relate to any individual characteristic that was assayed for. It proved advantageous to methanogenic digestion to fungally pretreat samples that had higher initial phenolic compound and colour concentrations, but disadvantageous for wastewaters with low initial phenolic compound and colour concentrations. Anaerobic digestion of fungally-treated and raw samples generally showed little difference with regard to total COD removal and final pH. The incorporation of white-rot fungus into a pretreatment process such as a jet loop reactor or rotating biological disc contactor could prove to be highly advantageous to cellar wastewater treatment.